2019
DOI: 10.1111/asej.12185
|View full text |Cite|
|
Sign up to set email alerts
|

Does Air Pollution Affect Consumption Behavior? Evidence from Korean Retail Sales*

Abstract: Using monthly regional panel data on air quality and large retail store sales in Korea, we empirically examine the effect of air pollution on retail sales. We account for regional heterogeneity in air pollution and control for various macroeconomic and climatic factors that can affect retail sales. We also use the air quality indicator in the west coastal islands (affected by trans‐border pollution but uncorrelated with the economic activity in the mainland) as an instrumental variable. The estimation results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Perhaps most surprisingly, warmer weather is strongly correlated with lead exposure (Levin et al 2020) (blood lead levels rise 10%-60% in warm weather). Pollution in turn has been linked to crime (Bondy, Roth, and Sager 2020), mental health (Gu et al 2020), mortality (Fan and Wang 2020), road accidents (Sager 2019), retail sales (H. Kang, Suh, and Yu 2019), house prices (Fontenla, Ben Goodwin, and Gonzalez 2019), mobility (C. Cui et al 2019), cognition (Peet 2020), and mood (Zheng et al 2019;Xinye and Wei 2019). Once again, it is difficult to argue that any variable in social science is not affected by some of these factors.…”
Section: Any Way the Wind Blows Doesn't Really Mattermentioning
confidence: 99%
“…Perhaps most surprisingly, warmer weather is strongly correlated with lead exposure (Levin et al 2020) (blood lead levels rise 10%-60% in warm weather). Pollution in turn has been linked to crime (Bondy, Roth, and Sager 2020), mental health (Gu et al 2020), mortality (Fan and Wang 2020), road accidents (Sager 2019), retail sales (H. Kang, Suh, and Yu 2019), house prices (Fontenla, Ben Goodwin, and Gonzalez 2019), mobility (C. Cui et al 2019), cognition (Peet 2020), and mood (Zheng et al 2019;Xinye and Wei 2019). Once again, it is difficult to argue that any variable in social science is not affected by some of these factors.…”
Section: Any Way the Wind Blows Doesn't Really Mattermentioning
confidence: 99%
“…In terms of consumer activities, Zhang and Mu ( 2018 ) documented a significant increase in mask consumption during periods of extreme air pollution, especially masks designed to protect against PM2.5. Kang et al ( 2019 ) empirically tested the relationship between air pollution and retail sales of consumer goods, finding that more severe air pollution was associated with a larger fall in retail sales. In addition, Li et al ( 2017 ) argued that air pollution would have a negative effect on sales of fuel-inefficient cars.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…With respect to the relationship between air pollution and customers' channel selection behavior, we assume that offline shopping will decrease and online purchasing will increase under severe air pollution. Retailing studies have found that the shopping environment (e.g., cleanliness, in-store air quality) affects consumers' purchasing behavior, and declining sales of stores are related to unpleasant circumstances (Kumar and Karande, 2000;Turley and Milliman, 2000;Nicholson et al, 2002;Chocarro et al, 2013;Kang et al, 2019). Meanwhile, evidence has shown that consumers have channel switching behavior among different channels (Reardon and McCorkle, 2002;Choi and Mattila, 2009;Avery et al, 2012;Kleinlercher et al, 2018;Li et al, 2020).…”
Section: Literature Review and Hypothesis Development The Impact Of Air Pollutionmentioning
confidence: 99%
“…In addition to the negative effects on health, high PM concentrations reduce urban residents' outings and interactions, decreasing consumption and reducing overall vitality ( 16 , 17 ). Specifically, when PM accumulates, people reduce such outdoor leisure activities as jogging, walking, cycling, and hiking, and workers' productivity declines, which has a negative economic impact ( 16 , 18 , 19 ). Health costs rise due to various diseases associated with PM ( 16 ).…”
Section: Introductionmentioning
confidence: 99%